Effect of Aerobic Exercise on Left Ventricular Connexin43 Expression and Distribution in Juvenile and Young Adult Rats - Rustiana Tasya Ariningpraja; ‪Dewi Irawati Soeria Santoso; Ahmad Aulia Jusuf; Alfrina Hany (Journal of Biomedicine and Translational Research, 2021)
Background: Gap Junction (GJ) plays a role in supporting the heart electricity. Connexin43 (Cx43) as the main protein constituent of GJ in left cardiac ventricle, will increase in number and slightly redistributed to the lateral sides of cardiomyocytes after aerobic exercise in adulthood. The effects of aerobic exercise that begin at childhood are not well known.Objective: This study aims to observe the effect of aerobic exercise which started from childhood on left ventricle Cx43 distribution.Methods: This study was conducted on 28 male Juvenile (4 weeks) and young adult (8 weeks) rats, divided into 7 groups: 1) Juvenile rats undergoing 4 weeks of exercise (E-J4); 2) Control E-J4 (C-J4); 3) Juvenile rats undergoing 8 weeks of exercise (E-J8); 4) Control EJ-8 (C-J8); 5) Juvenile rats undergoing 12 weeks of exercise (E-J12; 6); Young adult rats undergoing 8 weeks of exercise (E-Yo8); 7) Control E-J12 and E-Yo8 (C-JY128). Exercise group will undergo different length of duration, starting from week 4 until 12 weeks. Cx43 was identified by immunohistochemical staining and analyzed with ImageJ software. Comparison was analyzed using independent t-test.Results: Insignificant lower of total Cx43 expression in E-J4 (64200.45 + 4243.676 total area, p >0.05) compared to control. In contrast, a significant higher of total Cx43 expression was observed in EJ-8, EJ-12 and E-Yo8 (80152.95 + 3760.481, p = 0.001; 75596.775 + 3976.333, p = 0,002; 81216.85+ 2475.768, p = 0,000). Slightly higher of lateral Cx43 redistribution occurred in all aerobic exercise, with significant lateralization in E-J8 and E-Yo8.Conclusion: Aerobic exercise increases Cx43 and slightly redistributed to lateral myocytes under normal condition both in juvenile and young adult rats.